2003
DOI: 10.1034/j.1600-6143.2003.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Function and Morphology of Intestinal Autografts and Allografts in Outbred Dogs

Abstract: Although small bowel transplantation (SBTx) has become a clinical option, there have been few studies of long-term function and histopathology of intestinal grafts. Unrelated mongrel dogs received autologous (n = 4) or allogeneic (n = 11) orthotopic SBTx under oral cyclosporine. Intestinal graft function and routine/ immunohistopathology of full-thickness intestine were studied. Six allograft and all isograft recipients had comparable body weight gain and are currently alive (> 420 days). Five allograft recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Tanaka et al 5 observed progressive increase on transplanted fetal intestine, mainly 2 months after transplantation. Iwanami et al, 6 in dogs, verified that even denervated grafts are able to efficiently digest and absorb nutrients to support life. However, adaptive responses of the transplanted intestine, such as regulation of intestinal transit, may be impaired by neuromuscular injury associated with extrinsic denervation or ischemia.…”
mentioning
confidence: 99%
“…Tanaka et al 5 observed progressive increase on transplanted fetal intestine, mainly 2 months after transplantation. Iwanami et al, 6 in dogs, verified that even denervated grafts are able to efficiently digest and absorb nutrients to support life. However, adaptive responses of the transplanted intestine, such as regulation of intestinal transit, may be impaired by neuromuscular injury associated with extrinsic denervation or ischemia.…”
mentioning
confidence: 99%